Dampak Penambangan Timah di Laut Terhadap Ekosistem Terumbu Karang di Pulau Pemuja dan Malang Duyung, Kabupaten Bangka Barat, Provinsi Kepulauan Bangka Belitung - Indra Ambalika Syari; Mohammad Agung Nugraha; Mu’alimah Hudatwi (Journal of Tropical Marine Science, 2022)
The Province of the Bangka Belitung Islands has an ocean area of 79.9% which has the potential for fisheries and tourism as well as tin mining in the sea. This research was conducted in October 2020 in the coral reef ecosystem of Pemuja Island (near to the coastal) and Malang Duyung Coral (far to the coastal), West Bangka Regency. The method used is Line Intercept Transect (LIT). The results showed that the condition of the coral reefs on Pulau Pemuja was categorized as "damaged" with a live coral cover of 16.50% which was estimated to be due to the impact of tin mining in the sea, which was marked by a high mud cover (silt) of 48.698%. Coral Mortality Index (IMK) value of 0.75 which indicates the number of corals that died due to mud cover. The condition of coral reefs in Malang Duyung is in the "Good" category with live coral cover of 69.17%. Malang Duyung coral reefs are still affected by mining, which is indicated by the presence of a mud cover of 10.833% while the IM value of 0.15 also indicates that dead coral is still being found. The results showed that the composition of dead coral covered with is an impact of offshore tin mining. Mining locations near the coastal area have a greater impact than those far from the coastal.